Islamic Education and Digital Public Spheres: Democracy, Social Media, and Religious Learning - Al-Najmi, Ruwaiha; Al-Qaysi, Zareefa; Yanning, Shu (Universitas Muhammadiyah Surakarta, 2026)
The rapid expansion of digital public spheres has transformed the dynamics of Islamic education, religious authority, and democratic participation in contemporary Muslim societies. Social media platforms have democratized access to religious knowledge through decentralized learning, participatory interaction, and transnational communication. However, algorithm-driven digital environments have also intensified ideological polarization, misinformation, fragmented religious authority, and the commodification of religious discourse. These developments create significant challenges for Islamic education in maintaining epistemic integrity, democratic ethics, and inclusive religious engagement within digitally mediated societies. This article aims to critically examine the transformation of Islamic education in digital public spheres and to develop a conceptual framework for democratic Islamic education in the digital era. This research employed a qualitative interpretive approach integrating digital ethnography, thematic analysis, and critical discourse analysis. Data were collected through in-depth interviews, digital observations, and the analysis of religious content across multiple social media platforms involving Islamic educators, Muslim youth, and digital religious communities. The findings indicate that digital public spheres have shifted religious authority from institution-based legitimacy toward algorithmically mediated visibility and participatory engagement. While digital platforms enhance accessibility and civic participation, they also reinforce echo chambers, ideological contestation, and weakened epistemic trust. The proposed framework emphasizes Islamic ethical values, critical digital literacy, democratic participation, inclusive religious dialogue, and responsible digital engagement as foundational elements of democratic Islamic education. The framework contributes to interdisciplinary discussions concerning religion, democracy, digital society, and contemporary Islamic educational transformation